STRATEGI PENGEMBANGAN BISNIS PRODUK OLAHAN DAGING DI PT. SUMBER PANGAN JAYA CIKARANG – JAWA BARAT - Devi Oktaviani; Akhmad Riyadi Wastra; Eny Dwiningsih (AGRIBUSINESS JOURNAL, 2018)
Identification of internal and external factors was conducted to determine the factors that influence the business development of PT. Sumber Pangan Jaya by using analytical tools IFE matrix (Internal Factor Evaluation Matrix) and EFE matrix (External Factor Evaluation Matrix). Processing data using IFE matrix produced the factors that become a major strength in the business development of PT. Sumber Pangan Jaya, the variety of products offered with a total score of 0.350, and the factor that becomes weakness is the consumers not entirely from upper class society with a total score of 0.093. EFE matrix processing produce factors that are major opportunities in business development PT. Sumber Pangan Jaya, namely the continuity of raw materials from supplier with a total score of 0.300, and a factor that is the main threat, the rise in raw material prices with a total score of 0.106. IE matrix processing results illustrate the position PT. Sumber Pangan Jaya are in the division IV, which means a strategy aimed at Growth and Build. The result of the SWOT matrix obtained 9 alternative strategies developed by the company's position on the matrix IE, in this case the strategy might be implemented is intensive strategy (market penetration, market development, and product development) and integration strategy (forward integration, horizontal integration and backward integration). Based on the results of data processing with the matrix QSPM, there are nine strategic priorities that can be executed by PT. Sumber Pangan Jaya.